Travel and Transportation Building (Max Rigot Selling Co)
Travel and Transportation Building, now virtually completed on the grounds of Chicago's 1933 World's Fair. This building is nearly 1,000 feet long, and offers some new concepts in architecture never before attempted. The dome of the Travel and Transportation Building will house the railroad exhibit at "A Century of Progress."